Assessment of adolescent physical development using body mass index and body self-perception - Cherniakova , G.M.; Avdiievska, O.H.; Danylenko, H.M. (Medicni Perspektivi, 2024)
Underweight or overweight in children and adolescents is a serious public health problem. Self-perception is an important factor in promoting health, especially during adolescence. The purpose of this study is to assess the characteristics of self-perception of children with low body weight, normal body weight, overweight and obesity. This study was conducted in Kharkiv secondary schools in November 2021. The total number of participants was 14,853, of which 8,290 were girls and 6,563 were boys, aged 10-17 years. Using an online questionnaire, adolescents indicated their body weight and height, and also assessed their own health preserving activities. Diagnosis of being underweight, overweight and obesity was carried out in accordance with World Health Organization (WHO) standards. Body self-esteem was assessed using the following questions: “What do you think about your body?”; “How satisfied are you with your health?”; “How satisfied are you with yourself?”; “How can you assess your own health?”. According to the results of the examination based on BMI, it was found that 63.1±2.4% of adolescents have normal body weight. Overweight was detected in 12.3±1.1%, obesity – in 2.4±0.5%. 17.4±1.3% of participants were underweight, and 4.8±0.7% had body mass deficit. By their own assessment, 75.0% of children considered themselves to have “normal” body weight, another 15.0% considered their weight “more than normal,” and about 10.0% of adolescents considered themselves “lean.” Among boys, 61.0% had normal body weight. About 16.5% of boys were considered overweight, and 3.8% of boys were obese. Insufficient body weight was found in 14.08% of respondents, and 4.6% had big body mass deficit. Among girls, the percentage of participants with normal body weight was 64.8%. 8.95% of participants were considered overweight, 1.35% were obese. Almost 20.0% were underweight; a large deficiency was detected in 5.0% of girls. In order to carry out health promotion activities among schoolchildren, the sexual characteristics of self-perception of one’s own body and health problems among adolescents should be taken into account. Boys were almost twice as more satisfied with themselves and their health than girls, regardless of how they perceived their body (p<0.01). The number of boys with overweight and obesity was twice as high as girls (20.0% vs. 10.0%). At the same time, almost one in four girls and one in five boys were underweight and/or had body mass deficit. The systematic collection and analysis of data on the health-preserving behavior of adolescents is an important component of the development and creation of health care programs for the children’s population of Ukraine.